Perspectives on Neuroscience Education in Doctor of Audiology Programs. - Mondul, Jane A.; Hauser, Samantha N.; Racca, Jordan M. (Perspectives of the ASHA Special Interest Groups, 2025)
Purpose: The role of neuroscience in audiology is expanding, with growing evidence linking hearing and brain health. This highlights a need for robust neuroscience education in doctor of audiology (AuD) programs. However, the extent and consistency of neuroscience training across programs is unclear. This study aimed to characterize perspectives on the value of neuroscience education in audiology and to examine current neuroscience training in AuD curricula in the United States. Method: A mixed-methods approach was used to assess the perspectives of AuD students, clinicians, and educators (n = 537) on neuroscience and auditory evoked potentials (AEPs, a clinical application of neuroscience) education. Participants rated the importance of these topics broadly and within specific content areas. Clinicians and educators also rated their confidence in teaching these topics. Additionally, we reviewed curriculum requirements and prerequisites across AuD programs. Results: Participants strongly endorsed the importance of neuroscience and AEP education in audiology. Qualitative analysis revealed themes related to foundational knowledge for clinical practice and potential to advance the profession. Many suggested tailoring neuroscience training to clinically relevant content, while preparing audiologists for the future. Despite broad support, many AuD programs lack specific neuroscience coursework, and undergraduate neuroscience prerequisites are rare. Conclusions: While both neuroscience and AEP education are highly valued, integration of neuroscience into AuD curricula is inconsistent, leading to variability in training. Standardizing neuroscience content in AuD curricula could better prepare graduates for the evolving profession. Challenges and recommendations for implementing neuroscience coursework in AuD programs are discussed. Supplemental Material: https://doi.org/10.23641/asha.29968105